2012
DOI: 10.1016/j.jadohealth.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A Family Intervention to Reduce Sexual Risk Behavior, Substance Use, and Delinquency Among Newly Homeless Youth

Abstract: Purpose We evaluate the efficacy of a short family intervention in reducing sexual risk behavior, drug use, and delinquent behaviors among homeless youth. Methods A randomized controlled trial of 151 families with a homeless adolescent aged 12 to 17 years. Adolescents were recruited from diverse sites in southern California from March 2006 through June 2009 and assessed at recruitment (baseline), 3, 6, and 12 months later. Families were randomly assigned to an intervention condition with five weekly home-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
192
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(193 citation statements)
references
References 31 publications
0
192
1
Order By: Relevance
“…Although few studies testing HIV preventions for homeless youth were found, the majority of those studies reported limited impact on high risk behaviors (Booth, Zhang, & Kwiatokowsi, 1999; Gleghorn et al, 1997; Milburn et al, 2012; Rew, Fouladi, Land, & Wong, 2007). While knowledge can be increased among homeless youth (e.g., Nyamathi et al, 2013; Rew et al, 2007) and non-runaways (see review, McKay et al, 2004; Simoni, Nelson, Franks, Yard, & Lehavot, 2011), interventions to date have not dramatically reduced adolescent sexual risk taking (DiCenso et al, 2002; Picot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies testing HIV preventions for homeless youth were found, the majority of those studies reported limited impact on high risk behaviors (Booth, Zhang, & Kwiatokowsi, 1999; Gleghorn et al, 1997; Milburn et al, 2012; Rew, Fouladi, Land, & Wong, 2007). While knowledge can be increased among homeless youth (e.g., Nyamathi et al, 2013; Rew et al, 2007) and non-runaways (see review, McKay et al, 2004; Simoni, Nelson, Franks, Yard, & Lehavot, 2011), interventions to date have not dramatically reduced adolescent sexual risk taking (DiCenso et al, 2002; Picot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4,15,16 HIV/AIDS prevalence among U.S. homeless and runaway youth is estimated to be up to 11.5%. 17,18 Nonetheless, some studies have failed to find a correlation between length of homelessness and sexual risk behaviors, 15 indicating a need for further research.…”
mentioning
confidence: 99%
“…Service providers should take into consideration the experiences of early adultified youth by working to tailor programs to runaway and homeless youth who wish to maintain their autonomy by practicing inclusivity and being non-judgmental towards youths’ lifestyles (Darbyshire, Muir-Cochrane, Fereday, Jureidini, & Drummond, 2006; French, Reardon, & Smith, 2003). Furthermore, family-based interventions can take into account wider family issues in providing aid to youth who leave home (Milburn et al, 2012), especially in light of early adultification’s linkage to household conflict and discord.…”
Section: Discussionmentioning
confidence: 99%